2020
DOI: 10.1029/2020gl087212
|View full text |Cite
|
Sign up to set email alerts
|

Eurasian Cooling Linked to the Vertical Distribution of Arctic Warming

Abstract: Observations show that deep Arctic winter warming, extending from surface to mid-troposphere, has concurred with below-average temperature over central Eurasia. Modeling studies focusing on the response to Arctic sea ice loss have shown Arctic surface warming but no consistent atmospheric changes at midlatitude. Using a large number of simulations from coupled and uncoupled climate models, we show that Eurasian below-average temperatures are more frequent in winters with deep warming compared to shallow, near-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 56 publications
(77 reference statements)
8
64
0
Order By: Relevance
“…Our results are consistent with Xu et al (2019) and He et al (2020), who found that the vertical extent of warming over the Barents‐Kara Seas can help resolve differences in the strength of Arctic‐midlatitude linkages in historical simulations. While we primarily make use of one model (WACCM), we find that atmospheric thickness is also closely coupled to the Siberian High response in E3SM (Figure 4).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with Xu et al (2019) and He et al (2020), who found that the vertical extent of warming over the Barents‐Kara Seas can help resolve differences in the strength of Arctic‐midlatitude linkages in historical simulations. While we primarily make use of one model (WACCM), we find that atmospheric thickness is also closely coupled to the Siberian High response in E3SM (Figure 4).…”
Section: Discussionsupporting
confidence: 93%
“…It remains an open question how important the vertical extent of the tropospheric warming is in assessing Arctic-midlatitude teleconnections (He et al, 2020). This also has implications for improving our understanding of the intermodel spread of the eddy-driven jet response in the latest Coupled Model Intercomparison Project (CMIP) projections due to the competing "tug-of-war" effects between upper troposphere tropical warming and AA (Barnes & Polvani, 2015;Peings et al, 2018Peings et al, , 2019Vavrus, 2018;Zappa et al, 2018); although the amplification of tropical warming remains uncertain in model simulations (Santer et al, 2017).…”
Section: 1029/2020gl088583mentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of studies based on reanalysis data support an association between amplified Arctic warming (AAW) and changes in the large-scale circulation that are consistent with slower-moving planetary waves, while investigations using model simulations are split as to whether a robust connection exists 5 . What is abundantly clear, however, is that challenges remain in identifying cause-and-effect because the signal-to-noise ratio is small, many changes are happening simultaneously in the climate system, models tend to underestimate the atmospheric response 6 , 7 , and model physics critical to the linkage may be unrealistic or missing 8 . Meanwhile, the controversy about the Arctic’s role in changing midlatitude weather continues, as some new studies report little atmospheric response to AAW 9 , 10 while others identify a robust response 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The lower boundary conditions in the SIC‐EXP simulation capture the observed changes in Arctic sea ice and the changes in Arctic SST that are directly associated with the changes in sea ice but do not capture SST changes that are not directly related to variations in sea ice. Previous studies have suggested that the atmospheric response is weaker than in the real world by only taking the direct effects of SSTs and SIC changes into account, without considering the interactions and feedbacks between these variables (Deser et al, 2015; He et al, 2020; Mori et al, 2019).…”
Section: Methodsmentioning
confidence: 99%